2009
DOI: 10.1590/s0066-782x2009000700006
|View full text |Cite
|
Sign up to set email alerts
|

Lipoproteína (a) está associada com níveis basais de insulina em pacientes com Diabetes Mellitus tipo 2

Abstract: SummaryBackground: It has not been clearly established whether insulin resistance/deficiency leads directly to atherogenesis or through its association with other risk factors such as Lipoprotein(a) [Lp(a)].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 31 publications
0
5
0
3
Order By: Relevance
“…Some studies revealed a negative relationship between Lp(a) and serum insulin; studies speculated that higher Lp(a) levels among patients with a longer duration of type 2 diabe­tes may be attributed to lower plasma insulin levels in individuals. An in vitro study showed that insulin suppresses Apo(a) production in primary cynomolgus monkey hepatocytes [ 19 ]. This finding is inconsistent with our study, which showed a non-significant association between Lp(a) and serum insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies revealed a negative relationship between Lp(a) and serum insulin; studies speculated that higher Lp(a) levels among patients with a longer duration of type 2 diabe­tes may be attributed to lower plasma insulin levels in individuals. An in vitro study showed that insulin suppresses Apo(a) production in primary cynomolgus monkey hepatocytes [ 19 ]. This finding is inconsistent with our study, which showed a non-significant association between Lp(a) and serum insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with IFG yielded a lower risk (29%) of presenting elevated Lp(a) values in comparison to normoglycemic individuals. This behavior is intimately linked to the impact of insulin in the metabolism of Lp(a), where it has been attributed an inhibiting effect in the synthesis of Apo(a) in animal models [56], supported by inverse relationships observed between both molecules in population studies [57, 58]. Of all glycemic status subgroups, subjects with IFG presented the most augmented values of insulinemia, statistically different to those of the normoglycemics (19.23 ± 12.84 versus 14.17 ± 8.45 mg/dL; P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous reports regarding Lp(a) levels and T2D are conflicting [7]. Decreased Lp(a) levels in response to hyperinsulinemia [8,9] and a negative relationship between Lp(a) levels and the incidence of T2D have been reported previously [10,11]. In contrast, some studies have shown a strong positive association between T2D and elevated Lp(a) levels [12,13].…”
Section: Introductionmentioning
confidence: 99%